Law, Ethics, and Politics: Dynamics of Public Opinion on the Legality of Jokowi's Bachelor's Degree from the Perspective of Legal Science - Mesra, Romi (PT. NALURI EDUKASI PRESS, 2025)
This study aims to analyze the dynamics of public opinion on the legality of President Jokowi's bachelor's degree from a legal, ethical, and political perspective. This study uses a qualitative approach with a literature study method, examining legal documents, online news, and academic studies from 2019–2024. The results of the study show that legally, President Jokowi's diploma has been declared valid by the court and related educational institutions. However, public perception is still influenced by narratives on social media that are not based on legal evidence. From an ethical perspective, legal leadership is still required to be transparent and ethical so as not to lose moral legitimacy. The discussion also shows the importance of legal literacy and fair public communication in responding to political issues that contain the potential for disinformation. These findings conclude that synergy between law, ethics, and politics is needed to strengthen public trust in state institutions and legitimate leaders.